If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f = wm(m) Multiply mw * m f = m2w Solving f = m2w Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Simplifying f = m2w
| 3(y+3)=4(y-4) | | 15d+5=7d+61 | | x=56a+32a | | 5/2x+3/5x | | 5=7-1/4x | | 0=-.50x-1 | | 8x+18=2x+6 | | 8x-18=2x-6 | | 22x+40x=16x | | -4x-3=7x | | 3x-10=-x*x | | f=wm | | x=34a+21a | | 4x-9x-15=5x+4-15 | | 0=-x+1 | | 3x+5=2x+25 | | 15=3x+1+4x | | 4x-3=7x | | x=6y-4y | | -8f+36=52 | | Y+20.03=-12.27 | | 3(3+r)=27 | | 12=x/4 | | y+9=4(x-3) | | 8-6x=8(1-4x) | | b=rm+r | | 4x=3-(x+5) | | (1/4)X+(1/8)=(3/4)x-(7/8) | | -2x+7=y | | (4n^3+5)(3n+5)=0 | | f(x)=-16x^2+80x+1600 | | 13-1/3x=5 |